Impact Assessment of COVID-19 on Immunization Service for Children - Kharisma Nurul Fazrianti Rusman; Evi Martha (Universitas Airlangga, 2021)
Background: Coronavirus Disease 2019 (COVID-19) or the coronavirus disease caused by the SARS-CoV-2 virus has become a concern around the world, especially in Indonesia. As of January 31, 2021, the total cases of COVID-19 infection in the world reached 103 million with 2.22 million cases. The COVID-19 pandemic threatened to have an impact on health progress and particularly on children's development due to the obstruction of immunization services as a national program. Objective: This study aims to assess the impact of the COVID-19 pandemic on child immunization services. Methods: The method used was a narrative literature review conducted by synthesizing and analyzing 4 search engines including ProQuest, ScienceDirect, Pubmed, and SpringerLink. The search for this manuscript found 22 texts that matched the specified topic, namely the impact of the presence of COVID-19 on immunization services in children, searched for the keywords immunization, COVID-19, immunization service, and child. Results: The COVID-19 pandemic has an impact on changes in immunization services for children who have become obstructed, reduced service coverage, perceptions of parents reflecting the high demand for immunization, and an impact on health status, namely by carrying out routine immunizations resulting in trained immunity and generating immunity. Conclusion: COVID-19 has a special impact on child immunization services. Immunization services must continue to run and carry out according to applicable standards following local government policies by taking into account the principles and guidelines given. Collaboration between the government, the community, non-governmental organizations, and health professionals are needed to prevent a double burden during the COVID-19 pandemic.